Hospital epidemiology and infection control - Mayhall, C. Glen (LWW medical book collection., 2012)
Thoroughly revised and updated for its Fourth Edition, a comprehensive reference on hospital epidemiology and infection control. Written by over 150 leading experts, this new edition examines every type of hospital-acquired (nosocomial) infection and addresses every issue relating to surveillance, prevention, and control of these infections in patients and in healthcare workers. This new edition features new or significantly increased coverage of emerging infectious diseases, avian influenza, governmental regulation of infection control and payment practices related to hospital-acquired infections, molecular epidemiology, the increasing prevalence of community-acquired MRSA in healthcare facilities, system-wide infection control provisions for healthcare systems, hospital infection control issues following natural disasters, and antimicrobial stewardship in reducing the development of antimicrobial-resistant organisms.